Reducing dietary intake of linoleic acid of mouse dams during lactation increases offspring brain n-3 LCPUFA content. (July 2016) - Schipper, L.; Oosting, A.; Scheurink, A.J.W.; van Dijk, G.; van der Beek, E.M.
Abstract: Omega (n-)3 and n-6 long chain polyunsaturated fatty acids (LCPUFA) accumulation in the infant brain after birth is strongly driven by dietary supply of n-3 and n-6 LCPUFAs and their C18 precursors through breast milk or infant formula. n-3 LCPUFA accretion is associated with positive effects on neurodevelopmental outcome whereas high n-6 LCPUFA accumulation is considered disadvantageous. Maternal diet is crucial for breast milk fatty acid composition. Unfortunately, global increases in linoleic acid (C18:2n-6; LA) intake have dramatically increased n-6 LCPUFA and reduced n-3 LCPUFA availability for breastfed infants. We investigated the effects of reducing maternal dietary LA, or increasing n-3 LCPUFA, during lactation on milk and offspring brain fatty acids in mice. Offspring brain n-3 LCPUFA was higher following both interventions, although effects were mediated by different mechanisms. Because of competitive interactions between n-3 and n-6 fatty acids, lowering maternal LA intake may support neurodevelopment in breastfed infants. Highlights: Reducing maternal dietary LA results in lower milk LA content. Increasing maternal dietary n-3 LCPUFA increases milk n-3 LCPUFA content. Offspring brain n-3 LCPUFA was higher following both interventions.